A Clinical Study on Rabies - Akter, Farhana; Hoque, Mohammad Mahfuzul; Ahmed, Ershad Uddin; Faiz, Md Abul (Journal of Chittagong Medical College Teachers’ Association, 2015)
Rabies is a fatal but easily preventable disease became one of the major public health problems in Bangladesh. This study carried out in Infectious Disease Hospital (IDH) Dhaka, Bangladesh-to see different clinical presentation of rabies, to evaluate the incubation period and the interval between appearance of symptoms and time of death of the patients. All the clinically diagnosed cases of rabies referred to IDH were included in the study. The data was collected from the patient attendant by using a structured questionnaire. Among 101 patients-most of the cases (85.2%) came from rural area and children less than 15 years were major victims (61.4%). Majority of cases (87.1%) of rabies had history of dog bite. Though 50.5% patients received wound treatment, in only 5.9% cases it was adequate. Out of 23.8% patients having history of post-exposure vaccination, 75% of them received Nerve Tissue Vaccine (NTV) and 54% took vaccine in adequate doses and duration. Although 89.1% patient had history of WHO category III bite, none of them received Rabies Immunoglobulin (RIG). Furious rabies was seen in 97% cases. Majority (69.3%) patient develop rabies within 60 days of exposure and most of the rabies cases (68.4%) died within 72 hours. To prevent further human death from rabies and economic loss, educating people about preventive measures, Tissue Culture Vaccine (TCV) and RIG should be immediately introduced at primary health care level of Bangladesh. JCMCTA 2015 ; 26 (1) : 4-8